KAJIAN PERGERAKAN SEDIMEN DASAR DAN GERUSAN PADA SALURAN LURUS ALLUVIAL - Azwarman Azwarman (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
The movement of sediment on straight channel  especially on altitude area with the alluvial, scour sediment or erosion as well transportation sediments influential to change the form of channel is very .If we see the day of the day flow on the basis   of the move will undermined if the speed flow produce voltage critical shear,  exceed speed  and voltage shear allowable .Scour sediment larger on the stream velocity around the bend if compared to channel  on straight .Big  and small scour sediment depent also to stream velocity at the channel and also  depend kinds of the material   .Reseach done on straight up for flow in twist destroy the outside of the bend channel cliff always ,while on the part in the corner occured and large depositional hangs from the discharge of channel and morpologinya alittle depotional .Length of time jetting to achieved equilibrium (stabile) .Stabile condition achieved where there is balance between the sediment carried over with sediment incoming balanced and changes shape cross section almost nothing .  On probation review channel alluvial this  made six different   jetting time .but the discharge of the sama with  q=0,00354 m3/det and  D50=0,0004  and the tools sower of sand(sandfeeder) the installed on upstream channelKey words : discharge, material ,time  equilibrium,stream velocity